Pengembangan Media Pembelajaran Berbasis Google SketchUp dengan Konteks Rumah Adat untuk Meningkatkan Hasil Belajar Materi Balok - Danuarta, Refki Ekhsan; Widiawati, Widiawati; Lestari, Reza (Media Pendidikan Matematika, 2025)
This study aims to produce Google SketchUp-based learning media products with a valid and practical Besemah Traditional House context to improve student learning outcomes in block material. The development model used is 4D, which consists of the Define, Design, Develop, and Disseminate stages. In the Develop stage, the research was conducted through three activities, namely One-to-One, Small Group, and Field Test. The research was conducted on eighth-grade junior high school students, totaling 18 students. This research was motivated by the low learning outcomes of students in block material, which was caused by teacher-centered learning and the lack of learning media that supports visual and contextual understanding. Data was collected through interviews with teachers, validation questionnaires from experts (media, material, and language), practicality questionnaires from teachers and students, as well as pretest and posttest to measure student learning outcomes. Expert validation indicated a very high level of validity: 86.6% from media experts, 84% from content experts, and 92% from language experts, all categorized as highly valid. The validated media were then tested for practicality, achieving an average of 92.5% from teachers and 89.06% from students, both of whom categorized them as highly practical. Additionally, student learning outcomes showed improvement, with an average pretest score of 57.94 and a posttest score of 80.13. The N-Gain calculation yielded a score of 0.527, which falls into the moderate category. Based on these results, this educational media product is deemed valid, practical, and effective in improving students' learning outcomes on block-related material. Therefore, Google SketchUp-based educational media is worthy of consideration as an alternative in interactive and contextual mathematics learning processes.